Financial Determinants of Tax Avoidance: Empirical Study of Islamic Banks in Asia and COVID-19 Review - Salsabilla, Selfira; Kholid, Muamar Nur (Universitas Ahmad Dahlan, 2025)
This study investigates the effects of profitability, firm size, leverage, and financial constraints on tax avoidance in Islamic banks across Asia. The research model was tested both before and during the COVID-19 pandemic, using data obtained from the Osiris database. The sample consisted of 22 Islamic banks in Asia that had complete data and reported profits during the observation period from 2016 to 2023. The data were analyzed using balanced panel data regression with the assistance of EViews software. Tax avoidance was measured using both the Effective Tax Rate (ETR) and Book–Tax Differences (BTD). The results indicate that profitability has a significant positive effect on tax avoidance. Firm size demonstrates a significant negative effect on tax avoidance during the COVID-19 period. Leverage consistently shows a significant negative effect on tax avoidance, both before and during the pandemic. Financial constraints exhibit a significant positive effect only during the pandemic. The study offers several implications: (1) Islamic bank management should balance capital structure to avoid overreliance on leverage; (2) highly profitable banks are encouraged to maintain their reputation and public trust by ensuring tax compliance; and (3) regulators need to strengthen oversight, particularly in unstable economic environments.